2008
DOI: 10.1017/s002202990800352x
|View full text |Cite
|
Sign up to set email alerts
|

The rebodying of stirred yoghurt: interactions between proteins

Abstract: The aim of the present study was to identify the nature of bonds established between protein particles after stirring that are responsible for the texture improvement of stirred yoghurts, called rebodying. Using a constant model yoghurt at pH 4.4, the effects of changes in the physicochemical conditions at stirring were studied on the subsequent rebodying. Short term rebodying was measured as the changes in viscoelastic properties at 4 degrees C during 20 h after stirring, while long-term rebodying was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…The increase in G 0 after stirring was found as a two-stage process. G 0 increased first rapidly for 2 h then slowly for at least the following 22 h (result not shown), in accordance with other authors (Arshad et al, 1993;Cayot et al, 2003;Renan et al, 2008aRenan et al, , 2008b.…”
Section: Viscoelastic Propertiessupporting
confidence: 93%
“…The increase in G 0 after stirring was found as a two-stage process. G 0 increased first rapidly for 2 h then slowly for at least the following 22 h (result not shown), in accordance with other authors (Arshad et al, 1993;Cayot et al, 2003;Renan et al, 2008aRenan et al, , 2008b.…”
Section: Viscoelastic Propertiessupporting
confidence: 93%
“…Yoghurt viscosity increased by a factor of w5 during the storage period, while relaxation rate decreased from 74 to 65% (data not shown). Viscosity increase during storage was more important than that reported by Renan et al (2008). In the present study, apparent viscosity was measured with a T-type sensor with minimal gel disturbance.…”
Section: Stirred-style Yoghurtmentioning
confidence: 72%
“…Yoghurt apparent viscosity increased in the first and third week storage through a mechanism called rebodying or structure recovery. According to Renan et al (2008), short term rebodying it thought to be due to cooling and formation of elastic bonds between protein particles, while long-term rebodying is ascribed to over-acidification. Yoghurt viscosity increased by a factor of w5 during the storage period, while relaxation rate decreased from 74 to 65% (data not shown).…”
Section: Stirred-style Yoghurtmentioning
confidence: 98%
“…As well, van Marle (1998) and Körzendörfer et al (2018) found a relationship between larger microgels and higher induced syneresis results, suggesting that microgel size and syneresis are related. After shearing, the gel rebodying occurs during cold storage: the broken gel structure is modified, new structures build up, and yogurt viscosity increases (Cayot et al, 2003;Renan et al, 2008Renan et al, , 2009. Some authors have introduced the idea that microgels may affect stirred yogurt viscosity depending on their characteristics and interactions in the gel network.…”
Section: Introductionmentioning
confidence: 99%